Perbandingan Ekstrak Daun Mangga Bacang Dengan Ekstrak Daun Pepaya Dalam Menghambat Pertumbuhan Streptococcus Mutans - Cindy Amallia Prasasti; Benarivo Timothy G; Sri Yasa Hasibuan; Mangatas H.P Hutagalung; Molek Molek (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; dental caries dental tissue disease characterized by tissue damage, ranging from the surface of the enamel to the dentin, and extending to the pulp. Objectives; know the comparison of the effectiveness of mango leaf extract (Mangifera foetida L) and papaya leaf extract (Carica papaya) in inhibiting the growth of Streptococcus mutants. Method; a laboratory experimental study with a posttest design only in the vitro control group. The analysis used is Oneway ANOVA. Results; showed that the average inhibitory diameter of 50% mango leaf extract against the growth of Streptococcus mutants was 13.16 ± 0.27, and the average inhibitory diameter of 50% papaya leaf extract against the growth of Streptococcus mutants was 9.18 ± 0.23. Conclusion; that there are differences in the effectiveness of chopped mango leaf extract and papaya leaf extract against Streptococcus mutants.